Effect of Age on Egg Quality Traits in Native Chicken at Different Age of Measurements under Intensive System in Himachal Pradesh - Dinesh, Krishanender; Sankhyan, V.; Thakur, D.; Kumar, R.; Suman, M. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during December, 2023–October, 2024 at University Poultry Farm, Palampur on Native chicken for studying the external and internal egg quality traits at different age of measurements. A total of 300 freshly laid eggs were collected at 28, 40, 52, 64 and 72 week of age. External and internal egg quality traits viz. egg weight, egg length, egg width, shape index, shell thickness, albumen length, albumen width, albumen height, albumen index, yolk height, yolk width, yolk index, Haugh unit were recorded using standard procedure. Most of the egg quality traits differed significantly at different age of measurements (p<0.05). Egg weight increased as the age of the bird progressed. Shape index estimate revealed that eggs were oval in shape and having optimum built. Albumen height and Haugh unit declined with advancement of age and maximum value was recorded at 28 week of age. Yolk index estimate indicated that eggs were falling under criteria of extra fresh. Haugh unit value ranged from 77.41 to 87.98 with overall mean of 82.65 indicated that eggs were of better albumen quality. Egg weight showed positive, moderate to high and highly significant correlation (p<0.01) with egg length, egg width, albumen length and albumen width at 72 week of age. Results of present study indicated that age of birds significantly affect the external and internal egg quality traits. The data generated from this study would be useful in characterization of Native birds of Himachal Pradesh.